2018
DOI: 10.1038/s41598-018-25865-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel extracellular vesicle-associated endodeoxyribonuclease helps Streptococcus pneumoniae evade neutrophil extracellular traps and is required for full virulence

Abstract: Streptococcus pneumoniae (pneumococcus) is a major bacterial pathogen that causes pneumonia and septicemia in humans. Pneumococci are cleared from the host primarily by antibody dependent opsonophagocytosis by phagocytes like neutrophils. Neutrophils release neutrophil extracellular traps (NETs) on contacting pneumococci. NETs immobilize pneumococci and restrict its dissemination in the host. One of the strategies utilized by pneumococci to evade the host immune response involves use of DNase(s) to degrade NET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 71 publications
3
61
0
Order By: Relevance
“…These observations correspond with the findings of the clinical study performed by Tillet et al, who noted a 26% decline in mortality from pneumococcal meningitis after addition of DNase to penicillin therapy [68]. Studies detailing the NET-evading mechanisms proved that pneumococci can produce nucleases or modify the cell surface to avoid NET-mediated killing and to further disseminate to other organs [67,69,70]. Another strain of bacteria with the ability to survive in NETs is methicillin-resistant S. aureus [71].…”
Section: Cns Infectionssupporting
confidence: 82%
“…These observations correspond with the findings of the clinical study performed by Tillet et al, who noted a 26% decline in mortality from pneumococcal meningitis after addition of DNase to penicillin therapy [68]. Studies detailing the NET-evading mechanisms proved that pneumococci can produce nucleases or modify the cell surface to avoid NET-mediated killing and to further disseminate to other organs [67,69,70]. Another strain of bacteria with the ability to survive in NETs is methicillin-resistant S. aureus [71].…”
Section: Cns Infectionssupporting
confidence: 82%
“…This study showed that S. pneumoniae strain D39 increased transcription of competence, pyrimidine and heat shock genes in response to interaction with brain tissue. Jhelum and colleagues [86] also demonstrated that pneumococci have mechanisms to package DNA-degrading enzymes into vesicles, which in turn facilitates the destruction of neutrophil extracellular traps.…”
Section: Host and Microbial Interactions Host-pathogen Interactionsmentioning
confidence: 99%
“…The MVs are packed with sRNA molecules that bind to mRNA inside human lung cells and in this way quench the human immune response. Similarly, an extracellular DNase was identified in MVs from S. pneumoniae that blocks neutrophil activity and helps to evade the host innate immune response (Jhelum et al, 2018). Porin-loss, which is common in antibioticresistant strains of K. pneumoniae, impacts the MV composition and the host-inflammatory response.…”
Section: Immunomodulatory Effects Of Mvsmentioning
confidence: 99%